Growth and Yield of Strawberry Influenced by the Application of Phosphate Solubilizing Biofertilizer - Fitriatin, Betty Natalie; Nakayama, Masakazu; Endo, Kenji; Hindersah, Reginawanti; Ariani, Nabila Syifa; Oktaviani, Meira (Soilrens, 2025)
Phosphorus availability in soil is one of the main limiting factors in the cultivation of horticultural crops, including strawberries. Although the total phosphorus content in the soil is relatively high, most of it is in a form that is not available to plants. Phosphate solubilizing microbes (PSM) play an important role in increasing the availability of phosphorus through the mechanism of dissolving insoluble phosphate compounds into forms that can be absorbed by plants.This study investigates the effect of phosphate solubilizing biofertilizer on the growth and yield of strawberry. Biofertilizer used phosphate solubilizing bacteria (Bacillus velezensis, Burkholderia mallei) and phosphate solubilizing fungi (Pseudallescheria boydii;  Talaromyces islandicus;  Penicillium janthinellum;  Trichoderma harzianum). The experimental design is randomized block design five treatments, with seven replications. Treatments are control, bio-encapsule of P-solubilizing bacteria, bioencapsule of P-solubilizing fungi, phosphate solubilizing bacteria in carrier base on peat, and phosphate solubilizing fungi in carrier base on peat. The results of the experiment showed that the application of phosphate solubilizing fungi with compost and peat carriers significantly improved vegetative growth parameters, including plant height, leaf number, and crown diameter. Although no significant differences were observed in fruit yield, PSB in microcapsule form showed promising results in enhancing fruit weight and size.